Recommendations for a National Policy for Women’s Entrepreneurship in Chile - Araya, Francisca (2022)
This study identifies and characterizes the support programs in the Chilean ecosystem. These  programs  are  offered  from  both  the  public  and  private  sectors  for  women  entrepreneurship  intentions,  nascent  and  established  entrepreneurs.  We  revise  the  programs and propose recommendations for a national policy for women’s entrepreneurship. The analysis identified 69 programs, and a) confirms the public sector as the main driver of the female entrepreneurship ecosystem, mostly, allocating funding; b) demonstrates the accelerated creation of women-oriented entrepreneurial programs since the last study of 14 programs conducted in Chile by Mujeres del Pacífico in 2016; and c) shows that the COVID-19  pandemic  postponed  and  slowed  down  programs  aimed  at  networking  and  event generation, but accelerated the creation of content in the form of entrepreneurial education  and  training  programs.  The  analysis  of  this  inventory  of  programs  shows  the  need  to  formulate  a  clear  national  policy  on  women's  entrepreneurship  that  aligns  and  optimizes the efforts of the public sector.